2019
DOI: 10.1111/jfpe.13102
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of xanthan gum based on palm stearin/beeswax matrix as wall system

Abstract: Xanthan gum microcapsules (XGMC) were prepared by phase separation method based on palm stearin/beeswax (PS/BW) systems. XG microcapsules with high encapsulation efficiency were obtained at the preparation conditions of PS-to-BW ratio 7:3 and core-to-wall ratio 10:10. The inverted micrograph showed that the shapes of XGMC were mainly spherical, and the particle sizes of XGMC were chiefly distributed in the range from 40 to 300 μm. The XGMC curve of differential scanning calorimetry (DSC) illustrated that two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The %EE value was similar to the yield value for ambient-dried PEC, so it can be concluded that the losses of chitosan, xanthan gum, and ibuprofen during preparation, drying, grinding and sieving were uniform (15). The moisture content was approximately 10% or lower in all samples, presumably due to the hygroscopicity of the polymers, primarily xanthan gum (15,44). Also, the moisture content in ibuprofen-loaded PECs (6.81 ± 0.17% for I_AD and 4.96 ± 0.09% for I_SD) was lower than the moisture content in placebo PECs (10.23 ± 0.18% for P_AD and 8.60 ± 0.21% for P_SD), so this study confirmed that the drug entrapment into PECs may favor the microbiological stability of the carrier (15,28).…”
Section: Yield Entrapment Efficiency Ibuprofen Content and Residual M...supporting
confidence: 61%
“…The %EE value was similar to the yield value for ambient-dried PEC, so it can be concluded that the losses of chitosan, xanthan gum, and ibuprofen during preparation, drying, grinding and sieving were uniform (15). The moisture content was approximately 10% or lower in all samples, presumably due to the hygroscopicity of the polymers, primarily xanthan gum (15,44). Also, the moisture content in ibuprofen-loaded PECs (6.81 ± 0.17% for I_AD and 4.96 ± 0.09% for I_SD) was lower than the moisture content in placebo PECs (10.23 ± 0.18% for P_AD and 8.60 ± 0.21% for P_SD), so this study confirmed that the drug entrapment into PECs may favor the microbiological stability of the carrier (15,28).…”
Section: Yield Entrapment Efficiency Ibuprofen Content and Residual M...supporting
confidence: 61%
“…3 The physical and chemical properties of microcapsules depend on the wall material, and the appropriate wall material can effectively protect the core material. 12 Isolated soy protein (SPI) is an excellent wall material for microcapsules because of its low cost, natural abundance, excellent film-forming ability, good functional properties, and high protein content (>90%). 4,13,14 Although SPI has a good film-forming ability, the poor water sensitivity and mechanical performance of soy protein materials limit their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several wall materials including proteins, carbohydrates, and lipids were widely applied in food field 3 . The physical and chemical properties of microcapsules depend on the wall material, and the appropriate wall material can effectively protect the core material 12 . Isolated soy protein (SPI) is an excellent wall material for microcapsules because of its low cost, natural abundance, excellent film‐forming ability, good functional properties, and high protein content (>90%) 4,13,14 .…”
Section: Introductionmentioning
confidence: 99%